On the Cauchy problem for hyperdissipative Navier–Stokes equations in super-critical Besov and Triebel–Lizorkin spaces. (January 2023) - Baaske, Franka; Schmeisser, Hans-Jürgen
Abstract: In this paper, we study well-posedness of the Cauchy problem for hyperdissipative Navier–Stokes equations with initial data in super-critical Besov and Triebel–Lizorkin spaces. We prove existence and uniqueness of mild and strong solutions which are local in time.